The Analysis of Mathematical Literacy Ability in PISA Oriented Questions with Uncertainty and Data Content Based On Gender - Nasuha, Amelia Putri; Ammamiarihta, Ammamiarihta (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The study was carried out in the VIII class of junior school Baitul Aziz of the 2022-2023 school year aimed at analyzing learners’ literacy of mathematics skills on the matter of PISA oriented questions with uncertainty and data content. This research implemented a quantitative descriptive method with a cross-sectional research design. The participants of this research was learners of class VIII-1 and VIII-2 as many as 37 learners. The research data included a written test with data analysis by categorizing mathematical literacy abilities into 3 categories, they are low, medium and high. The outcome of the test showed that 1) the mathematical literacy abilities of male learners point to high levels of category at a percentage of 7.14%, a medium figure of 85.71%, and a low category of 7.14%; 2) female learner mathematical literacy abilities indicate at a high category of 17.37%, a medium category of 56.52%, and a low category of 26.09%; 3) it was concluded that the literacy of mathematics of the male learners is equal to the literacy of mathematics of the female learners because the largest percentage of the category falls at medium.